Erratum: Zamanpoore, M., Grabowski, M., Poeckl, M. & Schiemer, F. (2010) Two new Gammarus species (Crustacea, Amphipoda) from warm springs in the south-east pre-alpine area of the Zagros, Iran: habitats with physiological challenges. Zootaxa, 2546, 31–51. - Zamanpoore, M.; Grabowski, M.; Poeckl, M.; Schiemer, F. (Zootaxa, 2010)
(Erratum)